Effect of laser processing on the microstructure of the FeCrAl alloys - Geanta, Victor; Voiculescu, Ionelia; Tenciu, D; Baschir, L.; Stanciu, Elena Manuela; Pascu, Alexandru (My University, 2020)
FeCrAl alloys are currently investigated in order to determine their behaviour at high temperatures in different environments, both erosive and corrosive (solid, liquid or gaseous). Nowadays, FeCrAl are used in special applications such as engine parts or various components of generation IV nuclear power plant were liquid metallic media is used for cooling. These media (like Pb, Pb-Bi, Sn) provide an increased heat transfer capacity. To increase the alloys resistance in extreme conditions (corrosion, erosion, high temperature) some surface processing can be performed to obtain a protective layer which constitute an effective barrier against the destructive action of the working environment. This study presents the results obtained by laser surface processing of several experimental FeCrAl alloys. Metallographic aspects such as microstructure changes, layer thickness and grain refining have been analysed. The microhardness values obtained in the processed layers are analysed, in comparison with the base metal and the results show that laser processing can be beneficial in terms of hardness increasing and grain refinement of FeCrAl alloys.
Keywords: laser processing; microstructure; FeCrAl alloys; microhardness